The 11th Commandment: Thou shall be well and happy - Dingani, Annah (PINS-Psychology in Society, 2018)
[ B O O K R E V I E W ] Cederstrom, Carl & Spicer, André (2015) The wellness syndrome. Cambridge: Polity Press. ISBN 978-0-7456-5561-1 pbk. Pages 163 Over the last decade there has been an effusion of a wellness discourse that is not only circulating the corporate world but academic, religious and social communities as well. This wellness movement has emerged around empirical knowledge production about processes and mechanisms that make people feel happy. This wellness discourse is supplied with intellectual resources by interested institutions and individuals who on the surface level seem to have the general population’s health interest at heart, but on the other hand also seem to have a vested political interest or dependence on it.